The impact of macroeconomic and financial factors on shadow banking in the new EU member states - Kjosevski, Jordan; Petkovski, Mihail; Stojkov, Aleksandar (University of Rijeka, Faculty of Economics, 2020)
The goal of this paper is to examine the impact of macroeconomic and financial determinants of the shadow banking dynamics in the selected 11 new EU member states using yearly data from 1999-2018. We apply three methods: fixed effects model, the difference-GMM and the system-GMM (Generalized Method of Moments). Empirical results provide evidence that the most important factors are the developments in the financial sectors (insurance and pension sectors), banking sector, money market rate, as well as the general economic growth. We also found that global financial crisis has a negative impact on the shadow banking growth. From the results we may conclude that traditional banks, insurance sector and pension funds are complementary with shadow banking. This results was opening new issues for macroprudential policy, bearing in mind the Basel III norms. Namely, one of the main goals of Basel 3 is to reduce procyclicality of bank lending, and the rise of shadow banking may have an impact on both capital-based regulation and income-based limits.
Keywords: shadow banking; EU new member states; panel data analysis